Adaptation to hypoxia in the treatment of anemia in the rehabilitation of dysfunctional uterine bleeding in adolescent girls - Paweł Radziejowski (Kazimierz Wielki University, 2018)
Twenty two of 35 girls (aged 12-15 years) have received a course of interval hypoxic training (IHT) (10-12 daily séances) and conventional during treatment for juvenile dysfunctional uterine bleedings (JDUB) white the other 13 girls have received the drug treatment (control group). Clinical examination proved the IHT course a beneficial effect. A positive clinical effect was obtained after 5 séances; bleeding stopped in all patients after 8 séances of the IHT. The hemoglobin concentration significantly increased; oxygen consumption and body oxygen regimen (BOR) were normalized; the working capacity increased. Increases were observed in urine pregnandiol and in the amount of keratosic cells in vaginal smears. It was suggested that the IHT beneficial effect on patients with JDUB depended-both-on- the general stimulating influence of low oxygen partial pressure in the inhaled (pIO2) on the function of oxygen supply system and on the specific effect of low pIO2 on the hypothalamic-hyphophysis-ovarian system.